2018
DOI: 10.14738/abr.610.5449
|View full text |Cite
|
Sign up to set email alerts
|

Performance Appraisal and Employee Commitment in Abia State Civil Service: A Focus on Ministries of Education and Works

Abstract: This work focused on performance appraisal and employee commitment in Abia State Civil Service. The dynamic nature of employees' commitment to their Ministries made this investigation very necessary. The objectives of the study were; to find out whether objective evaluation of employee performance has a positive relationship with employee affective commitment, to ascertain whether subjective evaluation of employee performance has relationship with employee continuance commitment. To achieve this objective, a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The effect of performance appraisal system on organizational commitment was also reported and confirmed in previous studies ( Muhammad, 2022;Setiawati & Ariani, 2019;Obona & Sampson, 2021;Ahuja et al, 2018;Uchenna et al, 2018;Krishnan et al, 2018;Ackah & Yornu, 2019;Omusebe et al, 2013;Wahjono et al, 2016;Neha & Himanshu 2015;Iqbal et al, 2015;Arogundade et al, 2015;Farndale et al, 2011;Kuvaas, 2011;Jonsson & Jeppesen, 2012).…”
Section: Discussion and Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The effect of performance appraisal system on organizational commitment was also reported and confirmed in previous studies ( Muhammad, 2022;Setiawati & Ariani, 2019;Obona & Sampson, 2021;Ahuja et al, 2018;Uchenna et al, 2018;Krishnan et al, 2018;Ackah & Yornu, 2019;Omusebe et al, 2013;Wahjono et al, 2016;Neha & Himanshu 2015;Iqbal et al, 2015;Arogundade et al, 2015;Farndale et al, 2011;Kuvaas, 2011;Jonsson & Jeppesen, 2012).…”
Section: Discussion and Resultssupporting
confidence: 80%
“…Moreover, performance appraisal system is likely to positively improve affective commitment. A study conducted by Uchenna et al, (2018) andBolarinwa, (2017), also confirmed that performance appraisal system has a weak relationship with employee continuance commitment and positively affects affective commitment. To achieve study objectives, this study examined the main hypotheses which predict the significant influence of performance appraisal system on organizational commitment in Gaza Electricity Distribution Corporation (GEDCO).…”
Section: Discussion and Resultsmentioning
confidence: 79%
“…Moreover, the literature also suggests that the effectiveness of the performance appraisal system is linked to employee satisfaction and commitment. The findings of (Uchenna et al, 2018) emphasized that performance appraisal helps in clarifying employees' work expectations, fostering individual growth, and ensuring that pay structure incorporates performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In some organizations appraisal results may be used to determine relative rewards in the firm who should get merit pay increases, bonuses or promotions. Similarly, appraisal results can be used to identify poor performers who may require some form of counselling, demotion, dismissal or decreases in pay, Uchenna et al (2018). DeNisi and Kluger (2000) specify that feedback on performance is a determining segment of all management of performance appraisal.…”
Section: Review Of Related Literaturementioning
confidence: 99%